Proses Politis Dalam Pembentukan Undang-Undang Perlindungan Pekerja Rumah Tangga di Indonesia - Erowati, Maria Yohanista; Kuncoro Putri, Grace Joanessa (University of Merdeka Malang, 2024)
The advocacy process for the Draft Law on the Protection of Domestic Workers (RUU PPRT) in Indonesia has entered its 20th year, or the end of the fourth term of the five-year legislative period in Indonesia. All the steps and prerequisites set forth in Law Number 13 of 2022 jo Law Number 15 of 2019 jo Law Number 12 of 2011 concerning the Formation of Legislation have been fulfilled, but the process has stalled on the desk of the Chairman of the Indonesian House of Representatives and there has been no progress whatsoever to date. This research employs empirical legal research methods, and the author also conducted in-depth interviews with Domestic Workers who are victims, Domestic Workers' Organizations, Activists, Parliamentary Representatives, and relevant Ministries, as well as those involved in the advocacy process for this bill. The results of this research indicate that the legislative process of the PPRT Bill, which has been ongoing for 20 years and ended with the process being stalled on the Speaker of the House's desk, clearly shows the lack of political will among those in power to achieve social justice for all Indonesian people, especially Domestic Workers, and their indifference towards the common people.